PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2012-2015) - Amelia Fitri Diani; Hadi Sunaryo; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
AbstractThe main of this research are to examine the impact of dividend policy, thedebt policy and profitability though the value of company. The data that used onthis research is secunder data, that is a report of company’s debit in ConsumerGoods, listed in the Indonesia Stock Exchange (www.idx.co.id) annual report in2012-2015. The sampling method used in this study is purposive samplingmethod. Samples that passed the criteria in this study were 19 company inConsumer Goods. Data processing method used is descriptive analysis, theclassical assumption test, multiple linear analysis, F test, T test and the coefficientof determination test. The results showed that the dividend policy significantnegative effect on the value of the company and the debt policy has no effect onthe value of the company. As for the effect on the profitability of the company'svalue. Simultaneously, the house variable, DPR, DER, ROE significant effect thePBV. Furthermore, to examine determination of coefficient R2 value squard is0,0545 it means that the changing of dependent variable is caused by independentvariable that is 54,5%. While 45% the rest it is caused by other factor which isoutside from this research.Keyword: Dividend Policy, Debt Policy, Profitability and Firm Value.